2021
DOI: 10.1096/fj.202001912r
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of allergen‐induced histamine production by neutrophils

Abstract: Histamine is a critical inflammatory mediator in allergic diseases. We showed in a previous work that neutrophils from allergic patients produce histamine in response to allergens to which the patients were sensitized. Here, we investigate the molecular mechanisms involved in this process using peripheral blood neutrophils. We challenged these cells in vitro with allergens and analyzed histamine release in the culture supernatants. We also explored the effect of common therapeutic drugs that ameliorate allergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 63 publications
(130 reference statements)
2
5
0
Order By: Relevance
“…In this work we show the cell-signaling pathways involved in ECP production, in order to provide possible therapeutic targets. We found that PI3K and ERK1/2 MAPKS are activated in response to Ags (see Figure 5 ), matching previous results from our laboratory ( 24 , 25 ). They are both involved in the IgE-dependent L-selectin downmodulation ( 50 ), NF-κB activation, COX-2 expression ( 25 ), MMP-9 ( 51 ) and histamine release ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this work we show the cell-signaling pathways involved in ECP production, in order to provide possible therapeutic targets. We found that PI3K and ERK1/2 MAPKS are activated in response to Ags (see Figure 5 ), matching previous results from our laboratory ( 24 , 25 ). They are both involved in the IgE-dependent L-selectin downmodulation ( 50 ), NF-κB activation, COX-2 expression ( 25 ), MMP-9 ( 51 ) and histamine release ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…We found that PI3K and ERK1/2 MAPKS are activated in response to Ags (see Figure 5 ), matching previous results from our laboratory ( 24 , 25 ). They are both involved in the IgE-dependent L-selectin downmodulation ( 50 ), NF-κB activation, COX-2 expression ( 25 ), MMP-9 ( 51 ) and histamine release ( 24 ). In agreement with these results, PI3K and ERK1/2 MAPK are also required for Toll-like receptor-dependent ECP production by human eosinophils ( 52 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations